2011
DOI: 10.1007/s00595-009-4251-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the recurrence patterns of gastric cancer following a curative resection

Abstract: Locoregional recurrence, peritoneal dissemination, and distant metastasis were the most common recurrence patterns of gastric cancer following a curative resection. Each recurrence pattern is associated with specific clinicopathological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 29 publications
5
58
0
2
Order By: Relevance
“…In 2005, 300,000 mortalities and 400,000 new cases of gastric cancer were reported in China (2). Metastasis from gastric cancer typically occurs in the abdominal cavity, peritoneum, lymph nodes and liver (3). Metastasis limited to the brain is rare and prognosis in such cases is poor (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, 300,000 mortalities and 400,000 new cases of gastric cancer were reported in China (2). Metastasis from gastric cancer typically occurs in the abdominal cavity, peritoneum, lymph nodes and liver (3). Metastasis limited to the brain is rare and prognosis in such cases is poor (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Three-year disease free survival was used for the primary endpoint of this study because most relapses occur within 3 years after surgery [18]. Secondary end points included 3-year OS and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Three-year DFS was used for the primary endpoint of this study because most relapses occur within 3 years after surgery and is strongly correlated with 5-year OS [18]. A meta-analysis of individual patient data collected in randomized clinical trials found that DFS is an acceptable surrogate for OS in trials of cytotoxic agents for gastric cancer in the adjuvant setting and has been widely used in many trials, including the CLASSIC and SAMIT trial [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences usually present in the abdominal cavity, peritoneum, lymph nodes, and liver. 3,4 Isolated recurrence limited to bone and bone marrow is rare, and prognosis in such cases is poor. 5 We report a rare case of skeletal metastasis in a case of poorly differentiated gastric cancer after adjuvant chemo and a disease free period of seven months in 1 and half -year follow-up.…”
Section: Introductionmentioning
confidence: 99%